IMPROVING STUDENTS' READING COMPREHENSION USING WORD CARD MEDIA IN INDONESIAN LANGUAGE - Dinda Fitrotin; Isna Ida Mardiyana; Astien Diena Koesmini; Rukmiyati Rukmiyati (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The purpose of this study was to determine the increase in students' reading comprehension when using Indonesian word cards as media. This type of research is Classroom Action Research (CAR). This classroom action research was carried out in a cycle consisting of planning, action, observation, and reflection. the results of classroom action research that has been carried out in cycle I, from the initial to the last stages have been carried out properly as they should. But in cycle 1 there were only 54% of students who were complete in carrying out learning activities. KKM in this content is 70. The percentage of students who complete in cycle II then increases to 88%. Based on the results of the research conducted in class 1 at SDN MAJAH II Bangkalan, the researcher can conclude that there is an increase in learning outcomes in the Indonesian language subject about praise sentences with the help of word card media. This can be seen from the learning outcomes of grade 1 students, where there was an increase after the implementation of learning through the media game of word cards, praise sentences.